2007
DOI: 10.1590/s0103-50532007000700009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace amounts of copper in river and sea water samples by flame atomic absorption spectrometry (FAAS) after cloud-point preconcentration

Abstract: Este trabalho propõe um novo método de pré-concentração baseado em ponto nuvem para a determinação de cobre. O reagente 1,5-difenil-benzoína (Cupron) foi usado como complexante e Triton X-114 foi adicionado como surfactante. Após a separação das fases e diluição da fase rica em surfactante com metanol em meio acidificado foi feita a determinação do cobre por espectrometria de absorção atômica com chama (FAAS). O fator de enriquecimento do cobre, após a otimização das condições de complexação e otimização, foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In surface and ground water Co(II) is <1.0 µg L –1 in pristine areas and 1–10 µg L –1 in populated area and in seawater values are typically of the order of 0.02 nM and range from <0.01–0.1 nM , and can effectively be masked by the addition of dimethylglyoxime (20 μM) to the CL reagent . Goudarzi reported that Cu(II) concentrations in seawater and river water were 4.5 ± 0.1 and 5.8 ± 0.2 µg L –1 respectively. The US EPA has established 50 µg L –1 as the practical quantification limit for copper .…”
Section: Resultsmentioning
confidence: 99%
“…In surface and ground water Co(II) is <1.0 µg L –1 in pristine areas and 1–10 µg L –1 in populated area and in seawater values are typically of the order of 0.02 nM and range from <0.01–0.1 nM , and can effectively be masked by the addition of dimethylglyoxime (20 μM) to the CL reagent . Goudarzi reported that Cu(II) concentrations in seawater and river water were 4.5 ± 0.1 and 5.8 ± 0.2 µg L –1 respectively. The US EPA has established 50 µg L –1 as the practical quantification limit for copper .…”
Section: Resultsmentioning
confidence: 99%
“…As such, it is important to develop efficient, sensitive and selective methods for determination of trace amounts of copper. Some analytical techniques have been reported for copper determination including atomic absorption spectrometry (AAS), 9,13,14 inductively coupled plasma-atomic emission spectrometry (ICP-AES), 9 inductively coupled plasma-mass spectrometry (ICP-MS), 15 and electrochemical methods. 16 Although these methods have high selectivity and sensitivity, some drawbacks still exist.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have been published on the preconcentration of copper by the CPE method. In all mentioned studies, copper has been preconcentrated by the CPE method after the formation of sparingly water-soluble complexes with a suitable chelating agent such as 8-hydroxyquinoline (Oxine), diethyldithiocarbamate (DDTC), 1-(2-pyridylazo)-2-naph thol (PAN), 1-(2-thiazolylazo)-2-naph t hol (TAN) and 4-(2-pyridylazo)resorci nol (PAR), 4-(2'-thiazolylazo)-resorcinol (TAR), 2 -(2-thiazolylazo)-p-cresol (TAC), 2 -(2-thiazo ly lazo)-4-methoxyphenol (TAMP) and others [7][8][9][10][11][12][13]. The CP of non-ionic surfactants can be conveniently decreased or increased by the presence of different additives (i.e., organic and inorganic additives), thus providing a way to use non-ionic surfactants under various conditions [14].…”
Section: Introductionmentioning
confidence: 99%